2015
DOI: 10.1002/adfm.201500449
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Organic Framework Nanofilm for Mechanically Flexible Information Storage Applications

Abstract: 1wileyonlinelibrary.com of any digital gadgets, the information storage chips should also be made fl exible for wearable applications. [8][9][10][11] In view of this, the recently developed resistance random access memories (RRAMs), which received tremendous amount of attention as an alternative to the chargebased memories such as dynamic random access memory and fl ash memory, have distinguished themselves as promising candidates for fl exible and consumer electronic applications, with the advantages of simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
150
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(154 citation statements)
references
References 66 publications
4
150
0
Order By: Relevance
“…[2,[4][5][6] Resistive switching memories (or RRAM in short), which use bistable resistance states to encode and storage binary digital data, are considered as one of the most promising candidates for the next-generation information storage technology. [10][11][12][13][14] For instance, by depositing hafnium oxide directly on plastic substrate, Shang et al successfully made flexible RRAM device that can be bent to the strain level of 3.18%. [10][11][12][13][14] For instance, by depositing hafnium oxide directly on plastic substrate, Shang et al successfully made flexible RRAM device that can be bent to the strain level of 3.18%.…”
Section: Introductionmentioning
confidence: 99%
“…[2,[4][5][6] Resistive switching memories (or RRAM in short), which use bistable resistance states to encode and storage binary digital data, are considered as one of the most promising candidates for the next-generation information storage technology. [10][11][12][13][14] For instance, by depositing hafnium oxide directly on plastic substrate, Shang et al successfully made flexible RRAM device that can be bent to the strain level of 3.18%. [10][11][12][13][14] For instance, by depositing hafnium oxide directly on plastic substrate, Shang et al successfully made flexible RRAM device that can be bent to the strain level of 3.18%.…”
Section: Introductionmentioning
confidence: 99%
“…[97] Light can also stimulate the transition between two structural states in MOFs with special photochromic molecules as ligands or guests. [28,[107][108][109] However, there are still issues hindering their real-world application, as an increase to the switching rate to THz and higher is required, and minimization of the area of tuneable MOFs needs to be addressed. This effect is achieved based on the MOF's azobenzene side groups, which can undergo lightinduced reversible isomerization between two cis and trans stable states.…”
Section: Bistabilitymentioning
confidence: 99%
“…Wang et al reported Hong Kong University of Science and Technology 1 (HKUST-1) which was integrated with surfaceanchored metal-organic framework (SURMOF)-based resistive switching memory. [123] A forming voltage of 15 V was required to trigger the device. The ferrocene which is infiltrated guest molecules can be inserted inside the pores of the HKUST-1 material (Figure 5a).…”
Section: Mof-based Rerammentioning
confidence: 99%
“…a) Schematic image of HKUST-1 SURMOF films grown by liquid-phase epitaxy. Reproduced with permission [123]. Reproduced with permission [122].…”
mentioning
confidence: 99%